Boşnakların Önemli Cemiyetlerinden Olan Gajret’in Kuruluşu ve 1903-1914 Yılları Arasındaki Faaliyetleri - Abdula, Sevba (4th International Balkan Studies Congress Proceedings, 2025)
Between 1878 and 1918, Bosnia and Herzegovina was part of the Aust-ro-Hungarian Monarchy. In this period, a large number of Serbian, Croat, and Bosniak societies were founded in BiH. At the beginning of the 20th century, Bosniaks founded several important societies and organizations, such as the Muslim Agricultural Cooperative, the Muslim Shareholder Printing House, the First Muslim Credit Cooperative, and the El-Kamer - Muslim Roll and Gymnastics So-ciety. The societies mentioned above and organizations played an important role in the social and political life of Bosniaks in BiH. One of those, one can even say the most important one, is Gajret. This society was founded in 1903 to improve Bosniak society and providing assistance to students in Middle schools and uni-versities. This paper aims to explain the factors that led to the creation of this society and to show its work until the beginning of the First World War. When it comes to sources, archival sources, and issues of the newspaper Gajret, which was published from 1907-1914, were used in the preparation of this paper. This newspaper was published intermittently in the following intervals: 1907-1914; 1921-1922; 1924-1941, also a calendar called Gajret Society. Gajret Society publis-hed eight issues of the Gajret calendar for 1907/1908; 1915; 1937; 1938; 1939. Also, a book called Gajret: A Society For Supporting Muslim Students, its development and origin, written by the editors of Behar newspaper in 1903, as well as literatu-re such as a book called The Role of Gajret in the Social Life of Muslims by Ibrahim Kemura, The Struggle of Muslims for Religious and Waqf Autonomy by Osman Nuri Hadžić, Cultural, Educational, Humanitarian and Social Societies in BiH During the Austrian rule of Đorđe Pejanović were used. It can be concluded that the Gajret Society had a great influence on the creation of politics and public life of Bosniaks during the first years of the 19th century.